"Resistencia a la fuerza de tracción de incrustaciones de resina compuesta cementadas con cemento dual, In Vitro" - Cruzado Oliva, Fredy Hugo (2017)
ABSTRAC This research study, cross-sectional, observational and in vitro; was used to compare the tensile strength of two conventional AllCem (FGM) and Relyx Arc (3M) cements in Z350 (3M) composite resin inlays, using 17 seconds and upper and lower third molars free of caries of Recent extraction for each group; The tensile strength was measured quantitatively with the Instron 8801 universal test machine in Mpa with a speed of 2mm / min. The average tensile strength results obtained with conventional dual cement AllCem (FGM) were 22.75 ± 6.78 MPa. While for the conventional dual cement group Relyx Arc (3M) they were 24.44 ± 6.98 MPa. Thus, there was no significant difference (p> 0.05) between the tensile strength values in composite resin inlays with conventional AllCem (FGM) and Relyx Arc (3M) dual cement.